Macular edema after surgical treatment of rhegmatogenous retinal detachment – the possibilities of its prediction - E. V. Boiko; I. V. Khizhnyak (Acta Biomedica Scientifica, 2021)
The aim: to develop a mathematical model for predicting macular edema based on the informativeness of clinical and instrumental predictors of its occurrence.Materials and methods. To determine the risk factors for macular edema 64 patients (64 eyes) with macula-off rhegmatogenous retinal detachment complicated by proliferative vitreoretinopathy (grade Cp 1–2) were selected. A retrospective analysis of the surgical treatment results was carried out. The age of the patients ranged from 30 to 81 years (28 women and 36 men).Results. Using regression analysis, two signifi cant factors were identifi ed: the sum of 8 meridians of the visual fi eld before surgery (p = 0.015) and the number of detached quadrants (p = 0.021). Based on the identifi ed factors, a model was obtained for predicting the occurrence of macular edema in the postoperative period for the patients with rhegmatogenous retinal detachment. Conclusion. Based on the analysis of clinical and instrumental indicators in patients with rhegmatogenous retinal detachment, a mathematical model has been developed that allows predicting the occurrence of macular edema in the postoperative period.The application of the proposed prediction model makes it possible to determine the tactics of treatment (peeling of internal limiting membrane) and predict the appearance of macular edema at the preoperative stage.